G147 Ovulatory and menstrual patterns in the first postmenarcheal year: A systematic review. (24th May 2017) - Gunn, HM; Farrell, S; Tsai, MC; McRae, A; Steinbeck, KS
Abstract : Aims: An understanding of what constitutes a normal menstrual cycle during the first postmenarcheal year is a common concern of adolescent females, their parents and clinicians. However, limited high quality evidence exists to describe menstrual normality in adolescents. Too often, menstrual presentations are inappropriately dismissed or conversely over-investigated. This systematic review summarises literature regarding ovulatory and menstrual patterns in the first postmenarcheal year in healthy adolescents. Methods: A comprehensive search of the following databases was performed: MEDLINE, Pre-MEDLINE, Embase, Web of Science, CINAHL and the Cochrane Library. Eligible studies included primary research articles describing menstrual cycles, symptoms, or validated ovulatory data in healthy females during their first postmenarcheal year. Two authors independently selected studies, extracted data, and assessed evidence quality. Results: A total of 22 studies met inclusion criteria, of which nine were longitudinal, providing data for over two thousand participants. Thirteen studies recorded menstrual cycle and/or symptom data and fourteen measured ovulation. Heterogeneous methodology precluded meta-analysis. Mean menstrual cycle length ranged from 32 to 61 days. Polymenorrhoea was reported in no more than 11% participants, oligomenorrhoea in up to one third, 'irregular cycles' in up to 43.0% and prevalence of dysmenorrhoea ranged from 30% to 89%. Mean menses length was 4.9–5.4 days and 41% to 88% participants had menses of 4 or 5 days' duration. Prevalence of ovulatory cycles using luteal-phase serum or salivary progesterone or urinary pregnanediol was zero to 45%. However, 93% of studies used definitions and thresholds which would not be considered ovulatory in current clinical practice. Conclusion: Medical literature routinely presents menstrual and ovulatory information as fact. However, through the review of almost 80 years of data, it is apparent that we have far less evidence than previously assumed. Menstrual normality is inconsistently defined, limited robust ovulatory data are available and a mismatch exists between the high reported prevalence of dysmenorrhoea and the variable prevalence of ovulatory cycles. However, the wide variability in evidence compels us to support a broad scope of menstrual patterns during the first postmenarcheal year and advocate safe sexual practice throughout adolescence.